PENGARUH GAYA KEPEMIMPINAN, LINGKUNGAN KERJA DAN EMPLOYEE ENGAGEMENT TERHADAP KINERJA KARYAWAN PADA PT PLN (PERSERO) UPT MANADO - Verdiansyah, Yudha; Mas’ud, Masdar; Imaduddin, Imaduddin (Lembaga Penelitian, Publikasi dan Pengabdian Pada Masyarakat, 2025)
This study aims to examine the influence of leadership style, work environment, and employee engagement on employee performance at PT Perusahaan Listrik Negara (Persero) Transmission Implementation Unit Manado. The data in this research were obtained from employees of PT PLN (Persero) Transmission Implementation Unit Manado in 2025 who were willing to participate as respondents. This study used primary data by conducting field research through the distribution of questionnaires/statements to respondents. The sampling technique used was the census method due to the small sample size, where the sample consisted of the entire population, which totaled only 65 employees. Data analysis was conducted using descriptive statistical analysis and SPSS version 26.0. Based on the research results, it can be concluded that leadership style, work environment, and employee engagement have a positive and significant effect on the performance of employees at PLN (Persero) UPT Manado. These three factors work together to create an ideal working condition.